Changes in the Composition of Oils after the Application of the Physical and Chemical EOR-Technologies; AIP Conference Proceedings; Vol. 2051 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2018 (AMHS’18) - Chuykina D. I.; Savinykh Yu. V. Yurii Valentinovich; Stakhina L. D.; Serebrennikova O. V. Olga Viktorovna (2018, 2018)
Title screen